Halo café au lait spot inside Mongolian spot. - Bonifazi, E. (European Journal of Pediatric Dermatology, 2017)
There are only two papers in the literature reporting lesions similar to those here described (1, 2). In one of these reports (1) the Mongolian spot is present at birth; the café au lait spots arise after one month and at the periphery of all spots standing on the Mongolian spot appears a normal skin halo. It seems clinically that the Mongolian spot disappears around the café au lait spot. The Authors decided and managed to make 3 biopsies, 1 on the Mongolian spot, 1 on the halo and 1 on the café au lait spot, showing that the dermal melanocytes present in the halo area and those in the café au lait spot were different from those found in the dermis corresponding to the Mongolian spot. They were round, had no dendrites, had little melanin in the absence of any inflammatory phenomenon.